Pengingkaran Umat Islam terhadap Kewajiban Zakat Mal dan Analisis Pandangan Al-Qur’an Q.S. At-Taubah:60 - Febriant, Dinjino Evano; Abdurrosyid, Muhammad (Jurnal Pendidikan Agama Islam, 2024)
The aim of this research is to study the phenomenon of Muslims' denial of their zakat mal obligations and analyze the perspective found in the Al-Qur'an in surah At-Taubah: 60 regarding this matter. Studies show that many Muslims ignore zakat mal, even though Islamic teachings explain it clearly. Factors such as lack of religious understanding, economic difficulties, and lack of socialization about the social and economic benefits of implementing zakat can cause this neglect. Analysis of verses from the Koran, searching related literature, and collecting data from respondents representing various levels of Islamic society are qualitative research methods. The focus of the analysis is Verse 60 of Surah At-Taubah in the Qur'an, which determines who is entitled to receive zakat mal and how it is carried out. The research results show that zakat mal plays an important role in building social justice, reducing poverty, and supporting various aspects of life in Islamic communities. Even though the Qur'an clearly determines who is entitled to receive zakat mal, actual practice often deviates from these provisions. Therefore, to overcome the rejection of zakat malls, education, use of technology, legal supervision, and increasing mass media awareness are solutions. To conclude, a deep understanding of Islamic teachings, especially zakat mal, is very important so that Muslims can carry out this obligation correctly. In accordance with its teachings, Islamic society can produce a more just and prosperous society with shared awareness and commitment